Tobacco smoking as risk factor of laryngeal cancer - Konopelko, Michał; Padała, Olga; Krupa, Adrianna; Putowski, Maciej; Piasek, Ewa (Journal of Education, Health and Sport, 2019)
Introduction: Laryngeal cancer is one of the most common type of head and neck cancers. It develops due to spontaneous mutation or influence of external factors (physical, biological and chemical). Cigarette smoking is primary chemical risk factor of laryngeal cancers. Purpose: The aim of the review was to present a role of tobacco smoking in the causation of laryngeal cancer. State of knowledge: Many of studies performed past years confirmed the correlation between tobacco addiction and head and neck cancers. 75% of all head and neck cancers are caused by cigarette smoking, which contains thousands of chemicals. More than 60 of them are known as carcinogens. Summary: Laryngeal cancer is the most common head and neck cancer. The prevalence of laryngeal cancer is increased by several carcinogens including tobacco smoking, which is known as the major risk factor of this type of cancers.